OMNIBUS LAW ON JOB CREATION IN THE CONSTRUCTION SECTOR OF INDONESIA - Edison Hatoguan Manurung; Sri Gambir Melati; Dimas Pramodya Dwipayana (Yayasan Education and Social Center, 2022)
The job creation law, which functions to accelerate economic recovery, especially in the construction world, has been ratified by the DPR. This Law affects the regulation of the intervention authority in terms of the implementation of construction services, both for construction service providers and users of construction services, and the supervision of regional regulations regarding the construction sector's performance, which consider hindering investment. The Law expects to provide provisions for the construction world, namely job creation, worker competence, welfare improvement, increased worker productivity, and empowerment of regional construction workers. So, to ensure and supervise if this Law has a positive impact on the world of construction as we advance, the role of the DPR RI is vital. For this reason, caution needs in formulating the derivative rules. But over time, the construction community rejected these laws. So based on this background, this research aims to see the impact of the Job Creation Act on the construction world